The Effect of the Cavity Damping on Vehicular Evaluation using the Finite Element Method - FERREIRA, Tiago Simão; MAGALHÃES, Pedro Américo; MOURA, Frederico Luiz; FERREIRA, Timóteo Simão (Archives of Acoustics, 2016)
This work focuses on finding a numerical solution for vehicle acoustic studies and improving the usefulness of the numerical experimental parameters for the development stage of a new automotive project. Specifically, this research addresses the importance of modal cavity damping for vehicle exerts during numerical studies. It then seeks to suggest standardized parameter values of modal cavity damping in vehicular acoustic studies. The standardized value of modal cavity damping is of great importance for the study of vehicular acoustics in the automotive industry because it would allow the industry to begin studies of the acoustic performance of a new vehicle early in the conception phase with a reliable estimation that would be close to the final value measured in the design phase. It is common for the automotive industry to achieve good levels of numerical-experimental correlation in acoustic studies after the prototyping phase because this phase can be studied with feedback from the simulation and experimental modal parameters. Thus, this research suggests values for modal cavity damping, which are divided into two parts due to their behaviour: ξ(x) = -0.0126(x − 100) + 6.15 as a variable function to analyse up to 100 Hz and 6.15% of modal cavity damping constant for studies between 30 Hz and 100 Hz. The sequence of this study shows how we arrived at these values.